Exploring the path between depression, anxiety and 10-year cardiovascular disease incidence, among apparently healthy Greek middle-aged adults: The ATTICA study. (December 2017) - Kollia, Natasa; Panagiotakos, Demosthenes; Georgousopoulou, Ekavi; Chrysohoou, Christina; Yannakoulia, Mary; Stefanadis, Christodoulos; Chatterji, Somnath; Haro, Josep Maria; Papageorgiou, Charalabos; Pitsavos, Christos; ,
Highlights: Psychological distress constitutes a significant and independent predictor of cardiovascular disease. Three linking pathways in this association were revealed: sedentariness, inflammation and metabolic syndrome. Psychological distress acts as a mediator in the association between socioeconomic status and cardiovascular disease. Abstract: Objectives: Although there is substantial evidence that psychological factors play an important role in the onset and course of cardiovascular disease (CVD), less is known about their combined effect and the pathways by which they affect cardiovascular health. The present work aimed to prospectively explore the effects of depression and anxiety on the 10-year CVD incidence, in relation to other lifestyle determinants, as linking factors in the context of the ATTICA study.Study design/Main outcome measures: The ATTICA study is a population-based, health and nutrition prospective cohort study (2002–2012), during which 853 middle-aged participants without a history of CVD [453 men (aged 45 ± 13 years) and 400 women (aged 44 ± 18 years)], underwent psychological evaluations at enrollment. The latent trait of depression and anxiety combined measure was estimated and referred as " Psychological distress "; path analysis was applied to describe the relationships among the different factors. Results: " Psychological distress " was positively associated with the 10-year CVD incidence (adjusted OR per 10 units: 1.4, 95% CI: 1.1, 1.7). Three linking pathways were revealed: sedentariness, inflammation and metabolic syndrome. Moreover, " Psychological distress " mediated the association between socioeconomic status (SES) and CVD, with participants of low SES scoring higher on the psychological measure (adjusted linear regression coefficient b: −7.1, 95% CI: −9.7, −4.5). Conclusions: Lifestyle and clinical factors seem to link psychological distress with CVD development. Joint psychological assessments should be considered for inclusion in CVD preventive strategies, which should incorporate interventions for interrupting the linking pathways.